Identifying the Drivers of Demand for Government in Southern African Customs Union Countries - Dessus, Sebastien C. (World Bank, Washington, DC, 2020)
The size of government defined as the share of the public expenditure in GDP measures the magnitude of resources that are under the control of the public sector and available for reallocation across sectors, income groups and geographical locations. This note focuses on the determinants of governments’ size in Southern African Customs Union (SACU) countries.